If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -4 = 11x + -8 Reorder the terms: -4 + 15x = 11x + -8 Reorder the terms: -4 + 15x = -8 + 11x Solving -4 + 15x = -8 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -4 + 15x + -11x = -8 + 11x + -11x Combine like terms: 15x + -11x = 4x -4 + 4x = -8 + 11x + -11x Combine like terms: 11x + -11x = 0 -4 + 4x = -8 + 0 -4 + 4x = -8 Add '4' to each side of the equation. -4 + 4 + 4x = -8 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = -8 + 4 4x = -8 + 4 Combine like terms: -8 + 4 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 49282*49389= | | R/4=35/10 | | 5x-6-4x+8=0 | | 144=2x+x | | 7-2(3x-1)+4x=5 | | (5x-6)-(4x+8)=0 | | (x)(6-x^2)^1/2 | | -48-5a=3(5a+4) | | 4/4-3 | | X=45-1.2y | | 6-8n+4n=10-96 | | 3(3x)+1=-39 | | 1m/3+1/6=31/6 | | -78+19y+8=5(5y-5)-9 | | -5+2m=-6m-13 | | 277=p-6 | | -3x+3(-x-6)=66 | | 30=-9x+30 | | -1.25/1 | | 3x+3=5x+8 | | 4/3u=24 | | 3-3x=11+5x | | p(x)=2x^4-7x^3+3x^2+8x-4 | | 15x+10=10+30 | | 1.5=0.3+y | | 6-2x=12+4x | | 9.18+8.35z= | | -2y-11=3y+14 | | 9x-8+4x=7x+16+2x | | 74+-3n=n-22 | | 5*7(-2)(-4)= | | -1.25/1*10 |